Lighten up : love what you have, have what you need, be happier with less - Walsh, Peter, 1956- (Free Press, 2011)
"Lighten Up" offers a road map to creating a less-is-more life, and teaches readers how a life of less can actually be a life of great abundance. Features three audits designed to instigate life changes: a financial audit combined with assessments of the physical junk filling your homes and the emotional junk causing tension in your life.